ANALYZING FICTION IN THE NOVELS OF CHITRA BANERGEE DIVAKA RUNI’S - Sarita (International Journal of Multidisciplinary Research and Studies, 2021)
Chitra Banerjee Divakaruni was born in Calcutta in 1957, and she moved to the United States when she was nineteen years old. She attended Wright State University in Dayton, Ohio, for her master's degree in English, and then she continued her education by enrolling in the Ph.D. program at the University of California, Berkeley. She started her writing career. Career as a poet after the publication of their book titled The Reason for Nasturtiums (1990). Arranged Marriage, her debut collection of short stories, was honored with the American Book Award, the PEN Josephine Miles Award, and the Bay Area Book Reviewers Award. These honors helped pave the path for her to become a prominent author in the field of English literature. A film with the same name as one of Divakaruni's best-selling novels, The Mistress of Spices, has been made into a movie of the same name. Her most notable novels are The Mistress of Spices (1995), Sister of my Heart (1999), The Vine of Desire (2002), Queen of Dreams (2004), The Palace of Illusions (2008), One Amazing Thing (2010), Oleander Girl (2013), and Before We Visit the Goddess (2016). She is also the author of the Brotherhood of the Conch Series, which consists of The Conch Bearer (2003), The Mirror of Fire and Dreaming (2005), and Shadowland (2016). (2009). One of her collections of short stories is titled Arranged Marriage.